Placement quality has a greater impact on employability than placement structure or duration - Smith, C.; Ferns, Sonia; Russell, L. (2019)
© 2019 International Journal of Work-Integrated Learning. All rights reserved. This paper addresses the question of the relative importance of work-integrated learning placement quality, structure (whether part-time or full-time), and duration (in weeks), for producing employability outcomes. Additionally, we explore whether the quality of those placements is more, less, or equally important than the structure and duration. Drawing on responses to questions in a survey from 2,313 participants, 1,316 of whom had no placement experience and 997 of whom had had a placement experience, as part of their university studies, we tested a series of related hypotheses. After controlling for prior work-experience, results show that the quality of the placement experience is a greater predictor of a variety of employability outcomes than either structure of the placement experience or its duration. Findings will inform curriculum designers, practicum supervisors, and those interested in the outcomes of higher education.